Cape Verde : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper (PRSP) for Cape Verde. The PRSP presents an appropriately ambitious economic outlook, with real GDP growth projected to rise to 7 percent in 2007. The overall macroeconomic framework of the PRSP is based on a rising primary recurrent surplus and on the buildup of international reserves to back the exchange rate peg. But underlying this framework are assumptions of a containment of contingent liabilities, especially from planned privatizations, and a substantial increase in external support.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CR; Government; ISCR; Policy Option; Poverty